A novel aggregation-induced emission poly(phosphoramidate): fluorescence properties and visual detection for Cu2+. Issue 23 (11th October 2021) - Guo, Liulong; Yan, Hongxia; Wang, Lianlian; Yang, Pengfei; Yan, Lirong; Zhao, Yan
Abstract : A novel AIE poly(phosphoramidate) was synthesized through an ester ammonolysis reaction by using triethyl phosphate and diamines. Surprisingly, the obtained polymer is sensitive to Cu 2+ and can be used as an in situ visual detection agent for Cu 2+ . Abstract : Non-aromatic aggregation-induced emission (AIE) polymers have become a hot spot in the materials fields due to their low toxicity and excellent environmental friendliness. However, this kind of polymer usually suffers from insufficient fluorescence properties and limited varieties. Herein, we have synthesized a novel kind of non-aromatic AIE polymer—poly(phosphoramidate) (PPA) for the first time in consideration of the electron-rich properties of P atoms and excellent biocompatibility of phosphate esters. The PPA is synthesized through a green and facile one-pot ester ammonolysis of triethyl phosphate with ethylenediamine (P1–P3) or 1, 6-diaminohexane (P4). The synthesized PPA shows typical AIE characteristics and can emit bright blue fluorescence under UV light. We found that the molecular weight, terminal groups and chain length all have remarkable influence on its fluorescence properties. Transmission electron microscope (TEM) images and density functional theory (DFT) calculations reveal that the fluorescence of PPA can be attributed to the formation of a luminogen cluster and the electronic delocalization caused by through-space conjugation. Notably, PPA is sensitive to Cu 2+ and it can change the colour of CuCl2 solution from colourless to purple. Thus, this novel PPA not only enriches the species of non-aromatic AIE polymers, but also provides a convenient visual detection agent for Cu 2+ .